Cross-sectional study of the prevalence of prescription opioids misuse in French patients with chronic non-cancer pain: An update with the French version of the POMI scale - Kerckhove, Nicolas; Delage, Noémie; Bertin, Célian; Kuhn, Emmanuelle; Cantagrel, Nathalie; Vigneau, Caroline; Delorme, Jessica; Lambert, Céline; Pereira, Bruno; Chenaf, Chouki; Authier, Nicolas; , Poma Network; et al. (Frontiers in Pharmacology, 2022)
Public health issues related to chronic pain management and the risks of opioid misuse and abuse remain a challenge for practitioners. Data on the prevalence of disorders related to the use of prescribed opioids in patients suffering from chronic pain remains rather patchy, in particular because of the absence of a gold standard for their clinical assessment. We estimated the prevalence of prescription opioid misuse (POM), using a specific and validated opioid misuse scale (POMI-5F scale), in adults with chronic non-cancer pain. Nine-hundred-fifty-one (951) patients with opioids prescription and followed-up in pain clinics and addictology centers for chronic non-cancer pain (CNCP) completed the survey interview. The results suggest that 44.4% of participants have POM, accompanied by overuse (42.5%), use of opioids for effects other than analgesia (30.9%), withdrawal syndrome (65.7%), and craving (6.9%). The motivations cited for POM, apart from pain relief, were to calm down, relax and improve mood. POM was shown to be related to male sex (OR 1.52), young age (OR 2.21) and the presence of nociplastic pain (OR 1.62) of severe intensity (OR 2.31), codeine use (OR 1.72) and co-prescription of benzodiazepines (OR 1.59). Finally, despite the presence of three subgroups of misusers, no factor was associated with the intensity of misuse, reinforcing the view that distinguishing between strong and weak opioids is not appropriate in the context of use disorder. Almost half of patients with CNCP misuse their prescribed opioid. Practitioners should be attentive of profiles of patients at risk of POM, such as young, male patients suffering from severe nociplastic pain, receiving prescription for codeine and a co-prescription for benzodiazepine. We encourage French-speaking practitioners to use the POMI-5F scale to assess the presence of POM in their patients receiving opioid-based therapy.